Hubungan Faktor Lingkungan dengan Kejadian Diare pada Balita di Pulau Jawa (Analisis Data SDKI 2017) - Aditya Fika Maulana; Hari Basuki Notobroto (Universitas Airlangga, 2023)
Background: Toddler diarrhea is still a problem both globally and in Indonesia. Diarrhea remains one of the main causes of death among children under five. Environmental factors are one of the factors that can influence the incidence of toddler diarrhea. Objectives: To determine the relationship between environmental factors including sources of drinking water, toilet facilities and hand washing facilities in affecting the incidence of diarrhea in children under five in Java Island. Methods: This study uses a cross-sectional research design. The data used comes from the 2017 Indonesian Demographic and Health Survey (IDHS).. The study population was children under five in all provinces on the island of Java. The analytical method used is multivariate analysis with logistic regression. Result: There is a significant effect between the variable sources of drinking water (OR=2.188), toilet facilities (OR=1.848), and hand washing facilities (OR=2.040) with toddler diarrhea. Conclusion: Environmental factors, namely sources of drinking water, toilet facilities, and hand washing facilities, affect the incidence of toddler diarrhea on the island of Java.